Scedosporium apiospermum complex in cystic fibrosis; should we treat?. Issue 9 (15th May 2017) - Noni, Maria; Katelari, Anna; Kapi, Aikaterini; Stathi, Angeliki; Dimopoulos, George; Doudounakis, Stavros‐Eleftherios
Summary: Species of the Scedosporium apiospermum complex are the second most frequent filamentous fungi after Aspergillus fumigatus that can be found in cystic fibrosis (CF). Mixed colonisation by S. apiospermum complex and A. fumigatus is also quite common. In this study we summarise all CF patients who were colonised by S. apiospermum complex during their childhood and we present two CF patients who were treated as fungal bronchitis due to S. apiospermum complex. The medical records of 400 CF patients were reviewed in order to identify those with positive respiratory cultures for S. apiospermum complex. Scedosporium apiospermum complex was isolated in 10 CF patients and six of them had more than two positive sputum cultures during the study period. By the time of first isolation, the median age was 14.5 years, the median BMI was 19.41 kg/m 2, the median predicted FEV1 % was 78.65% and six patients had a history of A. fumigatus isolation. Two patients presented symptoms of infection while they were colonised by S. apiospermum complex. A rapid remission of their symptoms was observed only when antifungal therapy was administered. Antifungal treatment should be considered in CF patients who present symptoms of infection not responding to antibacterial therapy and S. apiospermum complex is persistently growing in sputum cultures.